THE EFFECT OF TAHFIDZ QUR’AN PROGRAM ON STUNDENTS ABILITY TO MEMORIZE THE AL-QUR’AN - Firyal Mumtazah; Sutiono Sutiono; Marliza Oktapiani (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
This research is motivated by the small number of memorizers of the Qur’an.there are so many people in Indonesia, but the number of memorizers is still very far away. As Muslims we should know how noble it is when we memorize the Qur’an because the Qur’an is a book that is a guide for human life. Memorizing the Qur’an is a necessity, you can imagine when no one memorizes the Qur’an, maybe there will not be the enormity of the beauty of the Qur’an in this world. In fact, everyone’s ability to memorize in different and with the Tahfidz Qur’an program,this will be the best bridge or solution. The method used in this study is a quantitative method. The research object is the Thafidz Qur’an program at SMAIT Buahati Islamic School Jakarta. the research sample consisted of 76 students, which is the entire population in class XI. Data collection techniques are carried out using observation, questionnaires, and documentation. While the data analysis technique uses analysis with the Wilcoxon test. Based on the result of the Wilcoxon test analysis in this study, asignificance level of 0,000 was obtained (P Value < 0,05), then H0 was rejected and Ha was accepted,therefore it can be concluded that the Tahfidz Qur’an program has an effect on the ability to memorize the Qur’an class XI students at SMAIT Buahati Islamic School Jakarta.